An Imaging Approach to Identify Mechanisms of Resistance to Pineapple Fruitlet Core Rot - Barral, Bastien; Chillet, Marc; Léchaudel, Mathieu; Lartaud, Marc; Verdeil, Jean-Luc; Conéjéro, Geneviève; Schorr-Galindo, Sabine (Frontiers in Plant Science, 2019)
Fruitlet core rot is one of the major postharvest disease of pineapple (Ananas comosus var. comosus). In the past, control strategies were designed to eliminate symptoms without addressing their causes or mechanisms, thus achieving only moderate success. In this study, (i) we focused on the anatomy of the fruitlets in the resistant “MD-2” and susceptible “Queen” pineapple cultivars; (ii) we identified the key role of the carpel margin in the infection process; (iii) we identified the key role of the sinuous layer of thick-walled cells in the inhibition of Fusarium ananatum colonization; and (iv) we linked the anatomy of the fruitlets with the phenolic content of cell walls. The fruitlet anatomy of the two cultivars was studied using X-ray, fluorescence, and multiphoton microscopy. Sepals and bracts were not perfectly fused with each other, allowing the pathogen to penetrate the fruit even after flowering. In fact, the fungi were found in the blossom cups of both cultivars but only became pathogenic in the flesh of the “Queen” pineapple fruit under natural conditions. The outer layer of the “MD-2” cavity was continuous with thick cell walls composed of ferulic and coumaric acids. The cell walls of the “Queen” blossom cup were less lignified at the extremities, and the outer layer was interspersed with cracks. The carpel margins were fused broadly in the “MD-2” pineapple, in contrast to the “Queen” pineapple. This blemish allows the fungus to penetrate deeper into the susceptible cultivar. In pineapple fruitlets, the hyphae of F. ananatum mainly progressed directly between cell walls into the parenchyma but never reached the vascular region. A layer of thick-walled cells, in the case of the resistant cultivar, stopped the colonization, which were probably the infralocular septal nectaries. Anatomical and histochemical observations coupled with spectral analysis of the hypodermis suggested the role of lignin deposition in the resistance to F. ananatum. The major phenolics bound to the cell walls were coumaric and ferulic acids and were found in higher amounts in the resistant cultivar postinoculation. The combination of fruitlet anatomy and lignification plays a role in the mechanism of host resistance to fruitlet core rot.